A prospective randomized controlled trial to determine the safety and efficacy of extracorporeal shock waves therapy for primary prevention of subclinical cardiotoxicity in breast cancer patients without a cardiovascular risk treated with doxorubicin - Song, Shinjeong; Woo, Joohyun; Kim, HyunGoo; Lee, Jun Woo; Lim, Woosung; Moon, Byung-In; Kwon, Kihwan (Frontiers in Cardiovascular Medicine, 2024)
Background: Doxorubicin is a highly effective anti-cancer drug that causes left ventricular (LV) dysfunction and induces late-onset cardiomyopathy. However, an effective and clinically applicable preventive treatment is yet to be discovered.Objective: Cardiac-Extracorporeal shockwave therapy (C-ESWT) has been suggested to treat inflammatory and ischemic diseases and protect cardiomyocytes from doxorubicin-induced cardiomyopathy. This study aims to assess the safety and efficacy of C-ESWT in the prevention of subclinical cardiotoxicity.Methods: We enrolled 64 breast cancer patients. C-ESWT group 33 patients were treated with our C-ESWT ( 200shots/spot at 0.09mJ/mm2 for 20 spots, 3 times every six weeks). The efficacy endpoints were the difference in left ventricular global longitudinal strain (LVGLS) change by 2D speckle tracking echocardiography and chemotherapy-related cardiac dysfunction (CTRCD). Echocardiography was performed on the baseline line and every 4 cycles of chemotherapy, followed by a follow-up 3,6 months after chemotherapy to compare the incidence of cardiomyopathy of subclinical LV dysfunction due to chemotherapy between the two groups.Results: Participants averaged 50±9 years in age, 100% female. In the results of follow-up 6 months after the end of chemotherapy, there was a significant difference in delta LVGLS between the C-ESWT group and the control group (LVGLS; -1.1±10.9% vs. -11.5±11.6% p-value; <0.001). A total of 23% (15 patients) of patients developed CTRCD (Control group; 13 vs. C-ESWT group; 2). C-ESWT was performed safely without any serious adverse events.In this prospective study, C-ESWT established efficacy in preventing subclinical cardiotoxicity, especially in breast cancer patients using doxorubicin chemotherapy, and the safety of C-ESWT Abbreviations